Question
upstudy study bank question image url

2. Utilice las reglas de derivación para derivar las siguientes funciones: \( \begin{array}{l}f(x)=x^{5}+5 x^{4}-10 x^{2}+6 \\ f(x)=\sqrt{\frac{x^{2}-3}{2 x+1}} \\ f(x)=\frac{e^{x}-1}{e^{x}+1} \\ f(x)=\frac{\ln x}{\sqrt{x}} \\ f(x)=\left(3 x^{2}+1\right) \sqrt{1-x^{2}} \\ f(x)=\sin \left(2 x^{3}+1\right)\end{array} \)

Ask by Garrett Jimenez. in Colombia
Dec 03,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

1. \( f'(x) = 5x^{4} + 20x^{3} - 20x \) 2. \( f'(x) = \frac{(2x)(2x+1) - 2(x^{2}-3)}{2(2x+1)^{2}\sqrt{\frac{x^{2}-3}{2x+1}}} \) 3. \( f'(x) = \frac{2e^{x}}{(e^{x}+1)^{2}} \) 4. \( f'(x) = \frac{2 - \ln x}{2x^{3/2}} \) 5. \( f'(x) = 6x\sqrt{1-x^{2}} - \frac{(3x^{2}+1)x}{\sqrt{1-x^{2}}} \) 6. \( f'(x) = 6x^{2}\cos(2x^{3}+1) \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Beyond the Answer

Para derivar estas funciones, emplearemos diversas reglas de derivación como la regla de la suma, la regla del producto, la regla del cociente, la regla de la cadena y las derivadas de funciones básicas. 1. Para \( f(x) = x^5 + 5x^4 - 10x^2 + 6 \), la derivada es: \( f'(x) = 5x^4 + 20x^3 - 20x \). 2. Para \( f(x) = \sqrt{\frac{x^{2}-3}{2x+1}} \), aplicamos la regla de la cadena: \( f'(x) = \frac{(2x)(2x + 1) - (x^2 - 3)(2)}{2(2x + 1)^2 \sqrt{\frac{x^2 - 3}{2x + 1}}} \). 3. Para \( f(x) = \frac{e^x - 1}{e^x + 1} \), utilizamos la regla del cociente: \( f'(x) = \frac{(e^x)(e^x + 1) - (e^x - 1)(e^x)}{(e^x + 1)^2} \). 4. Para \( f(x) = \frac{\ln x}{\sqrt{x}} \), de nuevo, aplicamos la regla del cociente: \( f'(x) = \frac{\sqrt{x} \cdot \frac{1}{x} - \ln x \cdot \frac{1}{2\sqrt{x}}}{x} = \frac{1 - \frac{\ln x}{2}}{x\sqrt{x}} \). 5. Para \( f(x) = (3x^2 + 1)\sqrt{1 - x^2} \), empleamos la regla del producto: \( f'(x) = (6x)\sqrt{1 - x^2} + (3x^2 + 1)(-\frac{x}{\sqrt{1 - x^2}}) \). 6. Para \( f(x) = \sin(2x^3 + 1) \), usamos la regla de la cadena: \( f'(x) = \cos(2x^3 + 1) \cdot (6x^2) \). ¡Listo! Con esto tienes las derivadas de todas las funciones solicitadas, cada una lista para brillar con su propio conjunto de propiedades matemáticas.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy